Pukis Bayam (Amaranthus Hybridus L.) dan Pisang Kepok (Musa Paradisiaca L.) untuk Mencegah Anemia: Uji Zat Besi dan Tingkat Kesukaan - Rose Yana; Sigit Yudistira; Desya Medinasari Fathullah; Nurul Hekmah (UNIVERSITAS NGUDI WALUYO, 2022)
The incident anemia in teenage girl is still quite high. One of the efforts to prevent anemia in teenage girl is to consume iron and vitamin C. Spinach and kepok banana are foods high in iron and vitamin C that can be processed into flour and made into pukis. Spinach and kepok banana can be processed into flour and made into pukis. Pukis is a snack that is liked by all people, especially for teenagers. This study aims to determine the iron content and hedonic scaling (color, aroma, texture, and taste) of pukis made from spinach and kepok banana. This research is an experimental study with a Completely Randomized Design (CRD) namely the formulation of spinach flour and kepok banana consisting of 4 treatments namely P0= 0%:0%, P1= 10%:5%, P2= 15%:10% and P3= 20%:15% with 3 replications. The research panelists consisted of 25 untrained panelists. The results of the iron content were tested by the Atomic Absorption Spectrophotometry (AAS) method and statistical analysis using the Kruskal Wallis test, while the hedonic scaling used the Friedman test. The result showed that the highest average iron content was P3 (1.612 mg/100 g) while the lowest iron content was P0 (0.087 mg/100 g). The results of Kruskal Wallis statistical analysis showed that there was an effect of formulation of spinach flour and banana kepok flour on the iron content of pukis (p=0.015). There was an effect of the formulation of spinach flour and banana kepok flour on the hedonic scaling (color, aroma, texture, and taste) of pukis (p=0.001). ABSTRAKKejadian anemia pada remaja perempuan masih cukup tinggi. Salah satu upaya untuk mencegah anemia pada remaja perempuan adalah dengan mengonsumsi zat besi dan vitamin C. Bayam dan pisang kepok merupakan bahan makanan tinggi zat besi dan vitamin C yang dapat diolah menjadi tepung dan dibuat menjadi pukis. Pukis merupakan makanan selingan yang disukai semua kalangan terutama remaja. Penelitian ini bertujuan untuk mengetahui kandungan zat besi dan tingkat kesukaan (warna, aroma, tekstur dan rasa) pukis bayam dan pisang kepok. Penelitian ini merupakan penelitian eksperimental dengan Rancangan Acak Lengkap (RAL) yaitu dengan formulasi tepung bayam dan tepung pisang kepok terdiri 4 perlakuan yaitu P0= 0%:0%, P1= 10%:5%, P2= 15%:10% dan P3= 20%:15% dengan 3 kali replikasi. Panelis penelitian berjumlah 25 panelis tidak terlatih. Hasil kandungan zat besi diuji dengan metode Atomic Absorption Spectrophotometry (AAS) dan analisis statistik menggunakan uji Kruskal Wallis, sedangkan tingkat kesukaan menggunakan uji Friedman. Hasil penelitian diketahui bahwa rata-rata kandungan zat besi tertinggi adalah P3 (1,612 mg/ 100 g) sedangkan kandungan zat besi terrendah adalah P0 (0,087 mg/100 g). Hasil analisis statistik Kruskal Wallis menunjukkan ada pengaruh formulasi tepung bayam dan tepung pisang kepok terhadap kandungan zat besi pukis (p=0,015). Ada pengaruh formulasi tepung bayam dan tepung pisang kepok terhadap tingkat kesukaan (warna, aroma, tekstur dan rasa) pukis (p=0,001).